Residential Aged Care : The last frontier for palliative care - Phillips, J.; Davidson, Patricia; Jackson, D.; Kristjanson, Linda; Daly, J.; Curran, Jim (Wiley-Blackwell Publishing Ltd, 2006)
Aim. This paper is a report of an explorative study describing the perceptions andbeliefs about palliative care among nurses and care assistants working in residentialaged care facilities in Australia.Background. Internationally, the number of people dying in residential aged carefacilities is growing. In Australia, aged care providers are being encouraged andsupported by a positive policy platform to deliver a palliative approach to care,which has generated significant interest from clinicians, academics and researchers.However, a little is known about the ability and capacity of residential aged careservices to adopt and provide a palliative approach to care.Methods. Focus groups were used to investigate the collective perceptions and beliefsabout palliative care in a convenience sample of nurses and care assistantsworking in residential aged care facilities in Australia. Thematic content analysiswas used to analyse the data, which were collected during 2004.Results. Four major themes emerged: (1) being like family; (2) advocacy as a keyrole; (3) challenges in communicating with other healthcare providers; (4) battlingand striving to succeed against the odds. Although participants described involvementand commitment to quality palliative care, they also expressed a need foradditional education and support about symptom control, language and access tospecialist services and resources.Conclusion. The residential aged care sector is in need of support for providingpalliative care, yet there are significant professional and system barriers to caredelivery. The provision of enhanced palliative care educational and networkingopportunities for nurses and care assistants in residential aged care, augmented by asupportive organizational culture, would assist in the adoption of a palliativeapproach to service delivery and requires systematic investigation.